PENGEMBANGAN BANGUNAN INFRASTRUKTUR AIR BERSIH DESA CINANGKA KECAMATAN CIAMPEA KABUPATEN BOGOR - Reska Ariyanti; Muhamad Lutfi (JPMUJ, 2023)
Cinangka Village is located in the Ciampea District, Bogor Regency, with a population of 500 people who do not yet have adequate clean water facilities to meet the needs of the villagers. So far, clean water supply facilities have been carried out in a simple way, in the form of taking water from a spring through a pipe, which is distributed to residents incompletely. The target of developing clean water in Cinangka Village this year is the integrated development of clean water facilities for all residents, especially in Cinangka Village. The methods for developing clean water facilities include: (1) Number of people in the next 10 years, (2) Determining the need for clean water in reservoirs, (3) Distribution of water from rivers with diesel pumps to water reservoirs, (4) ) Projection of the number of house connections (SR) connected to clean water facilities. The results and discussion obtained in the next 10 years are an increase in the number of residents of 672 people (112 families), with a planned debit of 2.6075 liters/second. The capacity of the water reservoir (reservoir) is 225.288 liters. The division of the distribution pipe is divided into 3 lines and the distribution of clean water can reach residents considering the location of Cinangka Village is in the hills. The development of clean water facilities in Cinangka Village can be realized with a budget plan (RAB) of Rp. 38,000,000.00.